Possible benefits of food supplementation or diet in scar management: A scoping review - Thibau Demarbaix; Ulrike Van Daele; Jill Meirte; Mieke Anthonissen; Koen Maertens; Peter Moortgat (SAGE Publishing, 2024)
Aim The evidence regarding a potential role of food supplementation as an adjunct therapy in scar aftercare is limited. In this scoping review we aim to provide an overview of the possible beneficial role of supplementations in aftercare settings. Method After formulating the research question and accompanying key words, a comprehensive search for relevant publications was performed using PubMed and Web of Science. Two authors independently identified and checked each study against the inclusion criteria. All data was collected and summarized for further discussion. Results After screening, 11 studies were included in the qualitative synthesis. Four studies including human subjects showed a promising connection between scar improvement and supplementation of vitamin D, omega-3 fatty-acids or a Solanaceae-free diet and lower omega-6 fatty-acid intake. Most of the studies were performed on in-vitro models. Preliminary evidence confirmed the beneficial role of vitamin D. Curcumin- and quercetin-supplementation were linked to decreased fibroblast proliferation. Vitamin C enhanced collagen production in healthy as well as keloidal dermal fibroblasts. Chitin stimulated cell-proliferation in human fibroblasts and keratinocytes. Conclusion The findings suggest early potential benefits of additional food supplementation in scar management for scars but provide no clear evidence. To establish guidelines or gather more evidence on food supplementation, studies involving human subjects (in vivo) are essential. The intricacies associated with nutritional studies in vivo present multifaceted challenges. It should be emphasized that substantial additional evidence is required before aspects such as timing and dosage of supplementation could be addressed for clinical application. Lay Summary Aim: This scoping review looks at whether taking food supplements might help with scar care alongside standard scar management following burn injury. Little information is thought to be available on this subject. An up-to-date review of the literature was undertaken to assimilate the body of evidence and determine if a consensus could be drawn. Method: A specific research question was designed and search conducted in scientific databases like PubMed and Web of Science. Two of our team members carefully selected and reviewed each study to determine which studies met the inclusion or exclusion criteria. All studies that met the inclusion criteria were then reviewed and the information collated to enable conclusions to be drawn. Results: Eleven studies met the inclusion criteria and were used to formulate the conclusions drawn. Four studies showed that taking vitamin D, omega-3 fatty acids, a diet without certain vegetables (Solanaceae), and eating less omega-6 fatty acids might help improve scars. It is important to note that most studies (seven out of 11) were carried out in a laboratory and not with real people. These lab studies showed that vitamin D might be helpful. Supplements like curcumin and quercetin seemed to slow down the growth of skin cells like fibroblasts and keratinocytes. Vitamin C aided collagen synthesis, which is important for healthy skin, in both normal and keloid scar cells. Another substance, chitin, was also found to help skin cells and keratinocytes grow better. Conclusion: Our findings point to some early possible benefits of taking extra nutrient supplements for managing scars but do not provide clear evidence. More research is required to enable the development of supplement recommendation and guidelines to be produced. Future research should focus on human trials but do keep in mind that carrying out supplement studies with people is more complicated. The evidence provided by this scoping review is insufficient to recommend the intake of any supplements or the imposition of dietary restrictions for the purpose of managing scars.